Pengaruh Jenis Ikan dan Konsentrasi Garam pada Rebung Ikan Terfermentasi - Ahmad Sapta Zuidar; Samsul Rizal; Kania Widyastuti (Balitbangda Provinsi Lampung, 2016)
Bamboo shoots can be fermented fish, known as Lemea in Bengkulu. Making lemea generally use freshwater fish, but the marine fisheries sector in Bandar Lampung potent enough, so we need to try to make one. Lemea has a distinctive flavor that is affected by salt. Therefore it is necessary to investigate the exact salt concentration in producing the best fish fermented bamboo shoots. This study aims to determine the effect of fish and salt concentrations in fish fermented bamboo shoots. Research arranged as factorial in complete randomized block design (RAKL). The first factor is the type of fish (J), namely J1 (mackerel) and J2 (carp). The second factor is the concentration of salt (G), namely (G1) 5%, (G2) 7.5%, (G3) 10%, (G4) 12.5%, and (G5) 15%. Data were analyzed further by testing HSD 5% and 1%. Observations made include the value of pH, total acid, total microbes, and organoleptic (color, aroma, texture, and overall acceptance). Results of analysis of variance showed that the type of fish affect the total acid and total microbes, whereas the effect on total salt concentration of acid, acidity (pH), total microbes, and organoleptic (color, aroma, texture). The best results were obtained in this study are the two types of fish that mackerel and carp with salt concentration of 5%, with a pH value of 5.3767, 0.0662% total acid, total microbes of 7.68 log cfu / g, color scores 2, 8 (white and gray), aroma score of 2.7 (acid), and the texture score of 3.8 (slightly soft).